Self‐healing encapsulation and controlled release of vaccine antigens from PLGA microparticles delivered by microneedle patches. Issue 1 (30th October 2018) - Mazzara, J. Maxwell; Ochyl, Lukasz J.; Hong, Justin K. Y.; Moon, James J.; Prausnitz, Mark R.; Schwendeman, Steven P.
Abstract: There is an urgent need to reduce reliance on hypodermic injections for many vaccines to increase vaccination safety and coverage. Alternative approaches include controlled release formulations, which reduce dosing frequencies, and utilizing alternative delivery devices such as microneedle patches (MNPs). This work explores development of controlled release microparticles made of poly (lactic‐ co ‐glycolic acid) (PLGA) that stably encapsulate various antigens though aqueous active self‐healing encapsulation (ASE). These microparticles are incorporated into rapid‐dissolving MNPs for intradermal vaccination. PLGA microparticles containing Alhydrogel are loaded with antigens separate from microparticle fabrication using ASE. This avoids antigen expsoure to many stressors. The microparticles demonstrate bi‐phasic release, with initial burst of soluble antigen, followed by delayed release of Alhydrogel‐complexed antigen over approximately 2 months in vitro. For delivery, the microparticles are incorporated into MNPs designed with pedestals to extend functional microneedle length. These microneedles readily penetrate skin and rapidly dissolve to deposit microparticles intradermally. Microparticles remain in the tissue for extended residence, with MNP‐induced micropores resealing readily. In animal models, these patches generate robust immune responses that are comparable to conventional administration techniques. This lays the framework for a versatile vaccine delivery system that could be self‐applied with important logistical advantages over hypodermic injections.